The very dizzy dinosaur - Tickle, Jack. (London : Little Tiger, 2005)
Dizzy Diplodocus waves his head this way and that, and if he doesn't watch his step he's bound to fall down flat.
Keywords: Pop-up books; 3D Books; Dinosaurs -- Fiction